Preservation of autochthonous shell beds by positive feedback between increased hardpart-input rates and increased sedimentation rates - Tomašových, Adam; Fürsich, Franz; Wilmsen, Markus (Journal of Geology, 2006)
The preservation of nonrapidly buried autochthonous shell concentrations with noncementing epifaunal animals in life position presents a taphonomic dilemma if in fact an increase in shelliness is driven by a decrease in sedimentation rate. A 150‐cm‐thick, densely packed shell bed with brachiopods from the Lower Jurassic of Morocco shows lower levels of postmortem alteration than shell‐poor beds, indicating that its formation is primarily governed by variations in hardpart‐input rates. Varying dominance and size structure of the main shell producer, brachiopod Zeilleria rehmanni, indicate that its increased population density was the main trigger in the shell bed formation. Thinner and less common microbial crusts in the shell bed than in shell‐poor beds indicate that higher shelliness is not due to lack of sediment. On the basis of actualistic data from modern mussel and oyster shell beds, the suspension feeding of a high‐density population leads to high biodeposition rates through production of feces and pseudofeces, which substantially exceed natural sedimentation rates. In addition, shell‐rich areas preferentially trap more suspended sediment than shell‐poor areas. Therefore, an increase in population density of shelly biodeposit producers should lead to higher biodeposition rates. This assumption is supported by a positive correlation between brachiopod shelliness and pellet abundance. Both active biodeposition and passive trapping of sediment would have increased sedimentation rate, thus leading to a decreased rate of shell destruction through suppression of predators or borers as well as stabilization and protection of the shell concentration. Under optimum ecologic conditions, these processes result in a positive feedback between an increased hardpart‐input rate and increased biogenic sedimentation rate. This scenario thus provides one alternative pathway for formation of well‐preserved shell concentrations formed by epifaunal suspension feeders. Identifying the importance of biodeposition is of environmental significance because it implies that carbonate sediment was produced largely in situ and was directly or indirectly related to the activity of shell producers. Recognizing the role of varying hardpart‐input rates in shell concentration genesis is of ecologic significance because shelliness can directly reflect abundance fluctuations of shell producers.
UnivIS-Import:2017-12-18:Pub.2006.nat.dgeo.IGM.LP.preser
Keywords: Autochthonous Shell Beds; sedimentation rate; brachiopods; Jurassic; Morocco